Examining the Influence of E-Payment System on LGAs’ Public Procurement Performance: A Case of Kasulu District Council, Kigoma Tanzania - Arthur, Begarving; Mwaseba, Nicodemas; Mnasi, Haji (Global Journal of Purchasing and Procurement Management, 2023)
Purpose: The study was conducted to examine the influence of e-Payment system on the performance of public procurement of Kasulu District. Methodology: The study employed a positivism philosophy and implemented a cross-sectional research design to answer research objectives. Data were collected from employees of Kasulu district council and suppliers that located in Kasulu district, Data were collected from 395 responded to questionnaires. Simple random sampling technique used to select sample. Data were analyzed using Statistical Package for Social Science (SPSS) Version 27; where Bivariate Regression analysis, descriptive analysis were conducted to answer the research objectives. Findings: The study revealed that the e-Payment System significantly and positively impacts public procurement performance. An increase in the execution of e-Payment System elements leads to improvements in various procurement aspects, including timely allocation of resources, increased value for money, better service quality, reduced user complaints, and improved communication. Unique Contribution to Theory, Practice and Policy: The study concluded by highlighting the importance of investing in and leveraging e-Payment Systems to optimize public procurement outcomes. The study recommended that the government prioritize and facilitate an enhanced technological environment to improve the effectiveness of public procurement within Local Government Authorities (LGAs).